Impaired self-awareness after traumatic brain injury: inter-rater reliability and factor structure of the Dysexecutive Questionnaire (DEX) in patients, significant others and clinicians - McGuire, Brian E.; Morrison, Todd G.; Barker, Lynne A.; Morton, Nicholas; McBrinn, Judith; Caldwell, Sheena; Wilson, Colin F.; McCann, John; Carton, Simone; Delargy, Mark; Walsh, Jane (Frontiers in Behavioral Neuroscience, 2014)
Aims: This study sought to address two questions: 1) what is the inter-rater reliability of the Dysexecutive Questionnaire (DEX) when completed by patients, their significant others, and clinicians; and 2) does the factor structure of the DEX vary for these three groups? Methods: We obtained DEX ratings for 113 patients with an acquired brain injury from two brain injury services in the UK and two services in Ireland. We gathered data from two groups of raters – “significant others” (DEX-SO) such as partners and close family members and “clinicians” (DEX-C), who were psychologists or rehabilitation physicians working closely with the patient and who were able to provide an opinion about the patient’s level of everyday executive functioning. Intra-class correlation coefficients and their 95% confidence intervals were calculated between each of the three groups (self, significant other, clinician). Principal component factor analyses were also conducted for each of the three groups. Results: The factor analysis revealed a consistent one-factor model for each of the three groups of raters. However, the inter-rater reliability analyses showed a low level of agreement between the self-ratings and the ratings of the two groups of independent raters. We also found low agreement between the significant others and the clinicians. Conclusion: Although there was a consistent finding of a single factor solution for each of the three groups, the low level of agreement between significant others and clinicians raises a question about the reliability of the DEX.